2002
DOI: 10.1128/jb.184.15.4304-4307.2002
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin Z of Escherichia coli : Reassessment of Its Regulation and Physiological Role

Abstract: Transcription of an aqpZ-lac fusion in a single copy on the Escherichia coli chromosome increased as cells entered the stationary growth phase. This was true in a variety of media, and increased transcription in enriched medium required the RpoS sigma factor. Expression of the aqpZ-lac fusion was not affected by up-or downshifts in osmolality. Disruption of aqpZ had no detectable adverse effects.Aquaporins belong to a large family of proteins that increase the rate of diffusion of water and glycerol across cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…The increased permeability for the wild type is apparently largely due to the incorporation of AqpZ into the cytoplasmic membrane. The permeability data we report here support the conclusion of Soupene et al that expression of aqpZ increases as cell growth slows and the cells enters stationary phase (9). Our results also indicate that AqpZ mediates water permeability in vivo.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…The increased permeability for the wild type is apparently largely due to the incorporation of AqpZ into the cytoplasmic membrane. The permeability data we report here support the conclusion of Soupene et al that expression of aqpZ increases as cell growth slows and the cells enters stationary phase (9). Our results also indicate that AqpZ mediates water permeability in vivo.…”
supporting
confidence: 81%
“…The observed relationships between the rate of growth and permeability in Fig. 1A, most notably the initial decrease in permeability and the lag that occurs between the observed increase in permeability and the onset of exponential growth, is consistent with the observation that transcription of an aqpZlac fusion on the chromosome of E. coli increases as the cells enter the stationary stage of growth (9).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Surprisingly, the B. abortus gene showed a behaviour different from that of the E. coli aqpZ gene, whose expression was reported to increase significantly in hypo-osmolar conditions, and to decrease in hyperosmolar conditions (Calamita et al, 1998), or found to be unaffected by changes in osmolality (Soupene et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…This result was again similar to that reported for E. coli (Calamita, 2000;Calamita et al, 1998), and indicated that the aqpX gene was subject to growth phase regulation. A recent report on the regulation of expression of the E. coli aqpZ gene using a single-copy chromosomal aqpZ-lacZ fusion indicated that expression of E. coli aqpZ increased in the stationary phase of growth and that this increase was dependent on the RpoS sigma factor (Soupene et al, 2002).…”
Section: Discussionmentioning
confidence: 99%